Geographic Market Definition: The Case of Medicare-Reimbursed Skilled Nursing Facility Care - John R. Bowblis; Phillip North (SAGE Publishing, 2011)
Correct geographic market definition is important to study the impact of competition. In the nursing home industry, most studies use geopolitical boundaries to define markets. This paper uses the Minimum Data Set to generate an alternative market definition based on patient flows for Medicare skilled nursing facilities. These distances are regressed against a range of nursing home and area characteristics to determine what influences market size. We compared Herfindahl-Hirschman Indices based on county and resident-flow measures of geographic market definition. Evidence from this comparison suggests that using the county for the market definition is not appropriate across all states.